LEGAL DISCOVERY REGARDING AGE LIMIT REQUIREMENTS FOR PRESIDENTIAL AND VICE-PRESIDENTIAL CANDIDATES IN GENERAL ELECTIONS (A Study of Decision Number 90/PUU-XXI/2023) - Siregar, Salman; Eddy, Triono; Koto, Ismail (Journal Analytica Islamica, 2025)
This study examines the legal aspects of the Constitutional Court (MK) Decision No. 90/PUU-XXI/2023, focusing on legal discovery, the age limit for presidential and vice-presidential candidates, and the legal consequences of the ruling. The research employs a normative juridical approach with a descriptive-analytical method, using statutory and case approaches and secondary data sources, including primary, secondary, and tertiary legal materials. The findings indicate that the MK ruling introduces new norms, positioning the Court as a positive legislature, with a ne ultra petita decision consistent with judicial authority principles. The minimum age limit of 40 years for candidates remains reasonable compared to global leadership trends (20-50 years). The principles of intergenerational and equality justice, as mandated by Pancasila's fifth principle, have been implemented since the 2024 election by allowing experienced young public officials to participate. The MK decision is final and binding, and must be accommodated by Parliament in forming or amending legislation, reaffirming the MK's role as the guardian and ultimate interpreter of the constitution